Sword of Heaven : Political Theology in Measure for Measure - Richard Wilson (Sillages Critiques)
This article revisits the long-standing debate on Middleton’s adaptation of the text of Measure for Measure for the 1623 Folio by suggesting that the idea of a double authorship, surprising as it may seem, is symbolically congruent with the play’s main plot and recurrent substitution themes. Indeed, Shakespeare and Middleton look like such strange bedfellows, the one with suspect Catholic connections in Stratford, the other an official of the City of London Protestant elite, that their alliance in the aftermath of the 1605 Gunpowder Plot, initially on Timon of Athens and Macbeth, suggests a shotgun marriage. Yet, textual research has established Measure for Measure beyond question as a ‘posthumous collaboration’, and ensured we can never go back to the sovereign Shakespeare. It was Middleton’s tampering with Shakespeare’s text that transformed it from a drama of demonic substitution, focused on the ‘outward-sainted deputy’ [3.1.93] into an allegory of divine sovereignty, idealizing the monarch as a deus ex machina. If Shakespeare editions have been slow to absorb the news from Vienna that the schizophrenia of Measure for Measure is a result not of authorial despair, but of its having been constructed by two dramatists of distinct generations and mentalities, working some sixteen years apart, they have nonetheless always registered resistance in the play to this totalitarian project of putting power on display.